2021
DOI: 10.3390/su13063364
|View full text |Cite
|
Sign up to set email alerts
|

Quantification of PV Power and Economic Losses Due to Soiling in Qatar

Abstract: Soiling losses of photovoltaic (PV) panels due to dust lead to a significant decrease in solar energy yield and result in economic losses; this hence poses critical challenges to the viability of PV in smart grid systems. In this paper, these losses are quantified under Qatar’s harsh environment. This quantification is based on experimental data from long-term measurements of various climatic parameters and the output power of PV panels located in Qatar University’s Solar facility in Doha, Qatar, using a custo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(6 citation statements)
references
References 11 publications
0
6
0
Order By: Relevance
“…The seventh study was conducted in Qatar, with an aim to experimentally examine the ecumenical loss due to the solar panels environmental challenge associated with dust. The data from the study showed that without clearing solar panels the output power would be reduced by 43% following six months of exposure to dust with average density of 0.7 mg/m 3 , which leads to economic losses if panels remain uncleaned [24].…”
Section: Economics / Managerial Barriersmentioning
confidence: 99%
“…The seventh study was conducted in Qatar, with an aim to experimentally examine the ecumenical loss due to the solar panels environmental challenge associated with dust. The data from the study showed that without clearing solar panels the output power would be reduced by 43% following six months of exposure to dust with average density of 0.7 mg/m 3 , which leads to economic losses if panels remain uncleaned [24].…”
Section: Economics / Managerial Barriersmentioning
confidence: 99%
“…Some researches categorized and conferred the dust problem based on its physical, chemical and biological properties [18]. Dust has been investigated within the last decades using several approaches [19][20][21]. Additionally, the relation amongst dust addition, tilt angle and orientation of PV modules has been investigated [22].…”
Section: Brief Review Of Similar Research Workmentioning
confidence: 99%
“…Many researchers investigate PV panels to estimate the best methods to increase efficiency. Some of this research is concentrated on the impact of dust accumulation on PV module performance, which fluctuates according to location, quantity of dust gathered, and cleaning frequency [19]. Research into dust and mud build-up has been made with PV modules in the Kingdom of Saudi Arabia (Dhahran).…”
Section: Pv Panel Efficiency and Its Maximizationmentioning
confidence: 99%